Mini Solar Power Resources for IoT system in the Vannamei Shrimp Pond Model - Widjaja, Damar; Seli Laka, Yohanes Priyanto (Universitas Sanata Dharma, 2025)
Shrimp pond water quality is one of the challenging issues for shrimp farmer to keep or even increase their production level to meet the domestic and export needs. Many researches have been done to help shrimp farmer to manage water quality using Internet of Things (IoT) technologies. In order to make all the devices in the IoT system work properly, it needs an adequate power supply. Mini solar power plant installation is an alternative way to give shrimp farmers an electricity power access when their area has no electricity power network. In this study, we propose the use of mini solar power plants to supply the power to IoT devices in shrimp pond model. There are two main sub-system in this model, i.e. power supply sub-system and IoT based monitoring and controlling sub-system. Power supply sub-system consist of solar panel, solar cell controller, battery, INA219 sensor, and LM2596 step down IC. IoT sub-system perform monitoring and controlling on two shrimp pond models with Arduino Mega microcontroller works as the main processor. The mini solar power system works well as it was designed. Mini solar power plant capable of charging the 12V 40Ah battery in 5 hours. In order to make the IoT system works, it only needs 75,6 Wh from 480Wh battery capacity.